Reinterpretasi Jihad dalam Pendidikan di Era Digital - Tian Wahyudi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This article examines the urgency of jihad in education and the role of the ummah in actualizing it in the digital era. The method used in this research is literature study, namely by collecting, selecting and sorting library materials relevant to the topics discussed, then analyzing and interpreting it. Jihad in Education is earnest effort for mukmin with all his abilities in order to provide a quality education intended for Muslims in ways that are in accordance with the guidance of the Shari'a in order to gain the pleasure of Allah. Jihad in education demands a collaborative role for all elements of the ummah, both their role as Muslim individuals and their role in the Muslim community. Jihad in education is very important to be actualized according to the role and abilities Muslim. As for the forms of jihad in education, namely: 1) jihad against lust as a basis for carrying out other jihad activities;2) Jihad parents in educating their children;3) jihad teachers in educating generations of ummah;4) jihad students in studying; 5) jihad assets used for the benefit of Islamic education;6) jihad through virtual media, namely by presenting educational and Islamic content in various digital media in various forms.